Design point analyses of solid oxide fuel cell‐steam cycle combined system: Effects of fuel reforming and bottoming cycle steam parameters. (5th April 2022) - Selvam, Kalimuthu; Rokni, Marvin M.; Komatsu, Yosuke; Sciazko, Anna; Kaneko, Shozo; Shikazono, Naoki
Summary: In the present study, the effects of the fuel reforming process and bottoming cycle steam parameters on the design point: energy efficiency/power output of large‐scale solid oxide fuel cell (SOFC) combined systems are investigated. The fuel reforming processes considered in this study are adiabatic steam reforming (ASR), partial oxidation reforming (POX), and autothermal reforming (ATR). For the bottoming cycles, subcritical (SubC), supercritical (SupC), ultrasupercritical (USC), and advanced ultrasupercritical (A‐USC) steam cycles are considered. The results show that the efficiency of the ASR‐combined system, which varies from 72.60% to 75.07% lower heating value (LHV) depending on the bottoming cycle, is the highest, followed by ATR (61.54%‐65.65% LHV) and POX (56.81%‐61.91% LHV) systems. On the other hand, the net power produced by the combined systems for a fixed SOFC cell area is in the reverse order, POX being the highest, followed by ATR and ASR systems. Even though the efficiency of the standalone A‐USC cycle is 10.25% points higher than the SubC steam cycle, the net efficiencies of the SOFC combined systems are less sensitive to the bottoming cycles, that is, 2.46% points difference between SubC and A‐USC for the ASR‐combined system, 5.11% points difference for the POX, and 4.11% points difference for the ATR systems. Parametric studies are also conducted for the oxygen to carbon ratio (O/C) and steam to carbon ratio (S/C) to investigate the suitable values in achieving the highest efficiency of the SOFC‐steam cycle combined system and minimum carbon deposition in the anode of SOFC. Abstract : Adiabatic steam reforming (ASR)‐solid oxide fuel cell (SOFC) offers the highest efficiency, followed by autothermal reforming (ATR) and partial oxidation reforming (POX)‐SOFC combined systems. POX‐SOFC produces maximum power, followed by ATR and ASR‐SOFC combined systems. The effect of bottoming steam cycles on the efficiency of the combined system is small.